Numerical Study on Steel Plate Shear Wall with Slit having Rectangular Opening - Zekaria, Adil; Ashenafi, Redeat (European Journal of Applied Sciences, 2022)
Steel plate shear wall with slit (SPSWS) is one of lateral load resisting systems that can be used in new buildings as well as in upgrading existing structures. It possesses efficient energy dissipation capacity and good ductility as a result of the installed slits within the infill steel plate. Cutouts might be required to let utility lines and other services pass through, for weight reduction and/or aesthetics. In this study, the effect of introducing rectangular cutout on SPSWS system will be examined under cyclic loading using finite element method. The paper considered the buckling load, ultimate bearing capacity, energy dissipation capacity, initial stiffness and stiffness degradation, ductility, and cracking patterns of the SPSWS. The parametric study includes: the effect of the presence of the vertical slits, thickness of steel plate and presence of edge stiffeners. The result showed that the presence of the vertical slits has highly minimized the negative effect of the rectangular cutout on the desired hysteretic behavior of the wall. Buckling resistance of slit wall with edge stiffeners tends to increase with cutting rectangular opening while it declines when the rectangular cutout is introduced to slit wall without edge stiffeners. It was also found out that when cutting a rectangular opening in the slit wall system, edge stiffener is more influential parameter than thickness of plate.